Carbon Nano-Onions Embedded CuO Nanosheets: An Excellent Stable Anode Material for Lithium Ion Battery. (March 2019) - Hao, Zhongjing; Qin, Meng; Li, Yueming; Lv, Xiaoju; Zhang, Dafeng; Wang, Qiushi
Abstract: Carbon nano-onions embedded CuO nanosheets was synthesized by hydrothermal method and this report reports the application of carbon nano-onions embedded CuO nanosheets in lithium ion battery anode materials. The introduction of carbon nano-onions leads to improved electrochemical performance. When applied to potential anode materials for lithium-ion batteries, the novel carbon nano-onions embedded CuO nanosheets deliver reversible discharge capacity of 709.7 mAh g −1 at 0.1 A g −1 and specific capacity of 167 mAh g −1 at 5 A g −1, much higher than those of the pure CuO nanosheets with same preparation conditions. In this paper, we demonstrate that the compositing of carbon nano-onions embedded CuO nanosheets is able to improve the performance significantly.